Maine Fisheries Program Complex. - U.S. Fish and Wildlife Service. ([Washingtonk, D.C.] : U.S. Fish and Wildlife Service, 2003)
"September 2003"--P. [4] of cover. Shipping list no.: 2004-0047-P. Cover title. Mode of access: Internet.